Rare Old Distal Carpal Row Dislocation: Wait, do not Reduce, or Operate - Muath Mamdouh Mahmod Al-Chalabi; Abdul Nawfar Sadagatullah; Wan Azman Wan Sulaiman (Gazi Medical Journal)
Carpal dislocations most frequently result from high-energy axial loading of the forearm with the wrist extended and can easily be overlooked. In this case, we conclude that stable, chronic dislocations with patient adaptation did not require any reduction or operation.